Integrating Culturally Responsive Islamic Madrasah Education (CRIMED) for Curriculum Reform: An SDGs-Based Inclusive Learning Framework in Indonesia - Arif Rahman; Maya Novita Sari; Hafidz; Imran; Marsekal Rahman Hakiem (Profetika: Jurnal Studi Islam, 2025)
Objectives:  This study aims to examine the implementation of Culturally Responsive Islamic Madrasah Education for Diversity (CRIMED) as an SDGs-based framework for curriculum reform that promotes inclusive and contextual learning in Indonesia. Theoretical framework: Grounded in the theoretical framework of culturally responsive pedagogy and Islamic educational philosophy, the study integrates principles of rahmatan lil ‘alamin, ta‘awun, and social justice with the global agenda of the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 10 (Reduced Inequalities), and SDG 16 (Peace, Justice, and Strong Institutions). Literature review: The literature review highlights gaps in existing Islamic education models that often emphasize normative content while underutilizing local cultural capital and inclusivity as drivers of sustainable development. Method:  Employing a descriptive qualitative approach, data were collected through document analysis, curriculum review, and in-depth interviews with madrasah teachers and institutional leaders. Result: The findings reveal that CRIMED operates through three interrelated domains. First, curriculum design integrates Islamic teachings with local cultural wisdom, enabling learning content to resonate with students’ lived experiences and diverse social contexts. Second, pedagogical practices emphasize participatory approaches, including project-based learning and contextual learning, which empower students to express cultural, religious, and social identities while developing critical thinking and collaboration skills aligned with SDG competencies. Third, institutional–community engagement strengthens the role of madrasahs as centers of social harmony, intercultural dialogue, and interfaith cooperation, contributing to peaceful and inclusive societies. The study demonstrates that CRIMED not only aligns Islamic education with national initiatives such as Religious Moderation but also situates madrasahs within the broader sustainable development discourse. Implications: The practical implications suggest that policymakers, curriculum developers, and educators can adopt CRIMED to enhance inclusivity, equity, and relevance in Islamic education. Novelty: The novelty of this research lies in positioning culturally responsive Islamic madrasah education as an explicit SDGs-based curriculum reform framework, offering a contextual yet globally relevant model for transforming Islamic education in multicultural societies.